2018
DOI: 10.1007/s10162-017-0653-5
|View full text |Cite
|
Sign up to set email alerts
|

Voice Discrimination by Adults with Cochlear Implants: the Benefits of Early Implantation for Vocal-Tract Length Perception

Abstract: Cochlear implant (CI) users find it extremely difficult to discriminate between talkers, which may partially explain why they struggle to understand speech in a multi-talker environment. Recent studies, based on findings with postlingually deafened CI users, suggest that these difficulties may stem from their limited use of vocal-tract length (VTL) cues due to the degraded spectral resolution transmitted by the CI device. The aim of the present study was to assess the ability of adult CI users who had no prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 86 publications
4
21
1
Order By: Relevance
“…There is some evidence that CI users can use combined F0-VTL cues in sentence contexts (Meister et al, 2016), but it is clear from the limitations of CI processing that it is easier for CI users to access F0 information. Age at implantation was related to use of VTL cues, but not F0 (Zaltz et al, 2018). Those who were implanted earlier had improved VTL discrimination, suggesting early exposure is important for taking advantage of VTL cues for talker discrimination.…”
Section: Role Of Different Acoustic Cuesmentioning
confidence: 89%
See 2 more Smart Citations
“…There is some evidence that CI users can use combined F0-VTL cues in sentence contexts (Meister et al, 2016), but it is clear from the limitations of CI processing that it is easier for CI users to access F0 information. Age at implantation was related to use of VTL cues, but not F0 (Zaltz et al, 2018). Those who were implanted earlier had improved VTL discrimination, suggesting early exposure is important for taking advantage of VTL cues for talker discrimination.…”
Section: Role Of Different Acoustic Cuesmentioning
confidence: 89%
“…Other studies found significant differences between groups in the manner by which listeners encoded vocal properties (see Section 3.5; Barone et al, 2016;Kovačić & Balaban, 2009;Meister et al, 2016;Zaltz et al, 2018). Another study examined whether topdown information, such as visual information, would influence listeners' gender rating of voices (Barone et al, 2016).…”
Section: Comparison To Individuals With Typical Hearingmentioning
confidence: 99%
See 1 more Smart Citation
“…One aspect of vocal timbre concerns the perception of cues in the acoustic signal that are related to VTL. Recent research has shown that CI users exhibit deficits in their ability to extract VTL cues, which could be a factor contributing to poor speaker and gender identification (Kovačić and Balaban, 2009;Massida et al, 2013;Fuller et al, 2014;Gaudrain and Başkent, 2015;Gaudrain and Baskent, 2018;Zaltz et al, 2018) and could contribute to difficulties in singing voice timbre perception as well.…”
Section: Introductionmentioning
confidence: 99%
“…Various tests for music perception have been proposed to investigate CI users’ abilities to use the information provided by electric hearing. These tests include the assessment of listeners’ capacities in the discrimination of pitch changes and pitch direction, the identification of melodies and timbres, as well as the processing of rhythms and emotions (e.g., Cooper et al, 2008; Looi et al, 2008; Nimmons et al, 2008; Kang et al, 2009; Brockmeier et al, 2010; Gaudrain and Başkent, 2018; Zaltz et al, 2018). While rhythmic processing is close to normal, CI listeners have been shown to be impaired in tasks requiring pitch discrimination or pitch direction judgments, even though inter-subject variability can be large (for reviews, see McDermott, 2004; Moore and Carlyon, 2005; Drennan and Rubinstein, 2008).…”
Section: Introductionmentioning
confidence: 99%